Microbial conversion of vegetable waste for flavor additives via solid-state fermentation: a comprehensive review - Janani Latha Ravi; Payel Ghosh; Faraz Ahmad; Shafiul Haque; Shafiul Haque; Paula Barciela; Franklin Chamorro; Ana Olivia Serra Jorge; Ana Olivia Serra Jorge; Miguel A. Prieto; Sandeep Singh Rana (Frontiers in Nutrition)
Flavor is a key factor in consumer choice and food acceptance. Currently, the vast majority of food flavor additives are produced by chemical synthesis. However, alternative production methods have been explored to meet consumer demands for “clean label” foods and “natural” additives. Consumer demand for natural products and the need for environmentally friendly processes are driving the development of novel biotechnology-based technologies for flavor synthesis. The bioproduction of dietary flavor molecules using plant waste has emerged as a viable possibility. This de novo synthesis in flavor production offers a way to create unique and desirable flavor compounds that are not readily available from natural sources. This study focuses on the creation of flavor molecules through microbial biotransformation, with particular emphasis on Solid-State Fermentation (SSF). SSF is a fermentation method in which microorganisms grow on a solid material without free-flowing water. Several microorganisms are used in SSF to produce flavor compounds, including the most commonly used fungi, but also lactic acid bacteria and yeast. The use of abundant and inexpensive vegetable waste produced by agro-industrial processing systems as a viable substrate for microbial flavor chemical production by SSF is highly encouraged from both sustainability and cost efficiency perspectives. Therefore, this review can serve as a basis for further studies aimed at developing effective and low-cost technologies for the extraction of essential flavors from agricultural residues.